Ama:nati as a Non-Material Value of Accounting Practices - Thalib, Mohamad Anwar (IAIN Kudus, 2022)
This study aims to find the value of local wisdom behind how students majoring in Islamic accounting from the Gorontalo tribe practice accounting. This study uses the Islamic paradigm. The approach chosen is Islamic ethnomethodology. The study results indicate that trust (Amanah) is a non-material value that is the leading spirit of Gorontalo ethnic students practicing accounting. The value of this mandate is reflected in the decisions of students who use educational assistance funds from the government to meet all needs related to supporting their education, such as buying books, paying for boarding houses, and laptops. In the culture of the Gorontalo people, this Amanah value is often advised by the elders through lumadu